Fast abdominal magnetic resonance imaging = Schnelle Abdomenbildgebung in der Magnetresonanztomografie - Budjan, Johannes; Schönberg, Stefan; Riffel, Philipp (RöFo, 2016)
Abdominal imaging is the driving force that necessitates the development of numerous techniques for accelerated image acquisition in magnetic resonance imaging (MRI). Today, numerous techniques are available that enable rapid, high spatial resolution acquisition for both T1 and T2 weighted images. These techniques open new opportunities in the detection and classification of numerous pathologies in the abdomen. However, there is still ongoing progress in the development of fast and ultrafast sequences and promising techniques are currently close to clinical application. With these 4D-technologies, MRI is becoming the central imaging modality for dynamic, motion-compensated imaging of the parenchymal abdominal organs such as liver, pancreas and kidney.
Gesehen am 14.06.2019